2022
DOI: 10.1093/ndt/gfac040
|View full text |Cite
|
Sign up to set email alerts
|

Design, recruitment, and baseline characteristics of the EMPA-KIDNEY trial

Abstract: Background The effects of the sodium-glucose co-transporter-2 inhibitor empagliflozin on renal and cardiovascular disease have not been tested in a dedicated population of people with chronic kidney disease (CKD). Methods The EMPA-KIDNEY trial is an international randomized, double-blind, placebo-controlled trial assessing whether empagliflozin 10 mg daily reduces risk of kidney disease progression or cardiovascular death in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(57 citation statements)
references
References 52 publications
0
45
0
1
Order By: Relevance
“…Notably, this cohort includes patients with glomerular disease (n ¼ 1669) and hypertensive/renovascular disease (n ¼ 1444). 58 The primary outcome of this trial was a sustained $40% decline in eGFR, ESKD, or death from renal or cardiovascular causes. The EMPA-KIDNEY trial was stopped early in March 2022 for efficacy suggesting that CKD patients without albuminuria also benefit from SGLT2 inhibitors and will soon markedly expand the population eligible for therapy.…”
Section: Patients With Ckd Without Albuminuriamentioning
confidence: 99%
“…Notably, this cohort includes patients with glomerular disease (n ¼ 1669) and hypertensive/renovascular disease (n ¼ 1444). 58 The primary outcome of this trial was a sustained $40% decline in eGFR, ESKD, or death from renal or cardiovascular causes. The EMPA-KIDNEY trial was stopped early in March 2022 for efficacy suggesting that CKD patients without albuminuria also benefit from SGLT2 inhibitors and will soon markedly expand the population eligible for therapy.…”
Section: Patients With Ckd Without Albuminuriamentioning
confidence: 99%
“…Conversely, a single preclinical study with a novel medicament that suggests harmful effects in experimental ADPKD can potentially lead to the unjustified exclusion of ADPKD patients from large clinical trials. Examples are the DAPA-CKD and EMPA-KIDNEY studies [ 167 , 168 ]. The DAPA-CKD found a promising attenuated rate of kidney function decline with the SGLT2 inhibitor dapagliflozin in subjects with chronic kidney disease and an elevated ACR.…”
Section: Extrapolating Treatment Efficacy From Animal Modelsmentioning
confidence: 99%
“…The DAPA-CKD concluded that regardless of the presence or absence of diabetes, the risk of a composite of a sustained decline in the estimated GFR of at least 50%, end-stage kidney disease, or death from renal or cardiovascular causes was significantly lower with dapagliflozin than with the placebo [ 115 ]. The scientific community now awaits the results of the EMPA-KIDNEY trial, which was recently reported to be “stopped early due to clear positive efficacy in people with chronic kidney disease“ [ 116 ].…”
Section: Sglt2 Inhibitors In Ckd—clinical Evidencementioning
confidence: 99%